2007
DOI: 10.3748/wjg.v13.i6.912
|View full text |Cite
|
Sign up to set email alerts
|

Use of probiotics for prevention of radiation-induced diarrhea

Abstract: AIM:To investigate the efficacy of a high-potency probiotic preparation on prevention of radiation-induced diarrhea in cancer patients. METHODS:This was a double-blind, placebo-controlled trial. Four hundred and ninety patients who underwent adjuvant postoperative radiation therapy after surgery for sigmoid, rectal, or cervical cancer were assigned to either the high-potency probiotic preparation VSL#3 (one sachet t.i.d. ,) or placebo starting from the first day of radiation therapy. Efficacy endpoints were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
235
1
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(248 citation statements)
references
References 18 publications
3
235
1
6
Order By: Relevance
“…No treatment-related toxicity was reported from the probiotic group. A larger cohort of similar subjects (n ¼ 490) from the same research team, using the same intervention, showed similar benefit [146]. Treated subjects showed a lower incidence of radiation-induced diarrhea (32% versus 52%; P < .001), less severe high grade diarrhea (1% versus 33%; P < .001), and fewer number of bowel movements (15 versus 5; P < .05).…”
Section: Intestinal Toxicitymentioning
confidence: 83%
See 1 more Smart Citation
“…No treatment-related toxicity was reported from the probiotic group. A larger cohort of similar subjects (n ¼ 490) from the same research team, using the same intervention, showed similar benefit [146]. Treated subjects showed a lower incidence of radiation-induced diarrhea (32% versus 52%; P < .001), less severe high grade diarrhea (1% versus 33%; P < .001), and fewer number of bowel movements (15 versus 5; P < .05).…”
Section: Intestinal Toxicitymentioning
confidence: 83%
“…Lower incidence of new disease, new metastases, or death; increased time to relapse [102,103] Probiotics in biliary cancer patients undergoing surgery; colorectal cancer patients undergoing chemotherapy; patients receiving abdominal and pelvic radiation Lower postoperative infection rates; decreased gastrointestinal toxicity (diarrhea) with less hospital care and less reduction in chemotherapy; decreased incidence of diarrhea [106,[143][144][145][146] Glutamine in variety of cancer patients undergoing chemotherapy and radiation Decreased rates and severity of mucositis, neuropathy, and intestinal toxicity; decreased use of pain medication in stomatitis patients; improved nutrition in stomatitis patients; improved ADL in neuropathy patients [112-119, 137-139, 148-150] Vitamin E topically in children undergoing bone marrow transplant; in adults undergoing chemotherapy or radiation to head and neck area Improved stomatitis [122,124,125] Zinc in head and neck patients during radiation therapy Improved stomatitis [126,127] (continued on next page) Chamomile extract as mouthwash in chemotherapy and radiation Improved stomatits sometimes [129,130] Homeopathic remedy including Arnica montana in chemotherapy Improved stomatitis [132] Proteolytic enzymes in head and neck patients with radiation…”
Section: Grifola Umbellatae In Bladder Cancermentioning
confidence: 99%
“…23 The probiotic VSL#3 has been investigated in a double-blind, placebo-controlled trial and led to fewer bowel motions and less diarrhea. 24 Several case reports have supported a role for hyperbaric oxygen therapy to enhance recovery, but its expense and limited availability make its routine use challenging. 25 …”
Section: Medical Managementmentioning
confidence: 99%
“…Assim sendo, em estudo de pacientes em radioterapia com comprometimento da pelve, a utilização do Lactobacillus acidophillus NDCO 1748, proporcionou diminuição significante da diarreia nesses indivíduos (54) . Em concordância, estudo duplo-cego em pacientes com neoplasia de cólon (15) , mostrou que o grupo placebo apresentou mais episódios de diarreia induzida pela radioterapia, em relação àquele que recebeu probióticos VSL#3 (51,8% e 31,6%, respectivamente; P<0,001), concluindo que o uso de bactérias probióticas é método fácil e seguro de proteção aos pacientes com câncer.…”
Section: Utilização Dos Probióticos Prebióticos E Simbióticos Em Pacunclassified